Microneedle-aided nanotherapeutics delivery and nanosensor intervention in advanced tissue regeneration - Churong Xu; Fei Wu; Zhouyi Duan; Bhavana Rajbanshi; Yuxin Qi; Jiaming Qin; Liming Dai; Chaozong Liu; Tuo Jin; Bingjun Zhang; Xiaoling Zhang (Journal of Nanobiotechnology)
Abstract Microneedles (MNs) have been extensively used as transdermal therapeutics delivery devices since 1998 due to their capacity to penetrate physiological barriers with minimal invasiveness. Recent advances demonstrate the potential of MNs in improving diverse tissue regeneration when integrated with nanometer-sized therapeutics or sensors. This synergistic strategy can enhance drug delivery efficiency and therapeutic outcomes, and enable precise and personalized therapies through real-time monitoring of the repair process. In this review, we discuss how optimized MNs (through adjustments in geometry, material properties, and modular structure), when combined with dimension- and composition-specific nanomaterials, enhance tissue regeneration efficiency. Moreover, integrating stimuli-responsive nanotherapeutics or nanosensors into MNs for spatiotemporal-controlled and targeted drug release, physiotherapy effects, and intelligent monitoring is systematically outlined. Furthermore, we summarize therapeutic applications of nanotherapeutics-MN platforms in various soft and hard tissues, including skin, hair follicles (HF), cornea, joint, tendons, sciatic nerves, spinal cord, periodontium, oral mucosa, myocardium, endometrium, bone and intervertebral discs (IVD). Notably, recent attempts using nanosensor-MN platforms as smart wearable devices for monitoring damaged tissues via interstitial fluid (ISF) extraction and biomarker sensing are analyzed. This review potentially provides tissue regeneration practitioners/researchers with a cross-disciplinary perspective and inspiration. Graphical abstract